Childhood disintegrative disorder and autism spectrum disorder: a systematic review. (13th December 2018) - Mehra, Chirag; Sil, Annesha; Hedderly, Tammy; Kyriakopoulos, Marinos; Lim, Ming; Turnbull, Jessica; Happe, Francesca; Baird, Gillian; Absoud, Michael
Abstract : Aim: In an attempt to clarify the debate surrounding the diagnostic validity of childhood disintegrative disorder (CDD), we systematically reviewed its characteristics and compared it with autism spectrum disorder (ASD). Method: Four databases were searched (PubMed, PsycINFO, Embase, and Web of Science). Included articles had participants with CDD, as defined by symptoms present in the criteria of the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision and the International Classification of Diseases, 10th Revision. Comparison groups were those with ASD and ASD with regression. Case studies were excluded. Results: Twenty articles, comprising 96 participants with CDD (80 males, 16 females), were included. Most studies were cross‐sectional. The prevalence of CDD was 1.1 to 9.2 per 100 000, with a mean age at regression of 3 years 2 months (SD 1y 1mo), with a range of 2 years to 7 years. In addition to core CDD symptoms, most had intellectual impairment, anxiety, challenging behaviours, and regressed in toileting skills. Participants with CDD and ASD shared core diagnostic and extra‐diagnostic features. However, participants with CDD seemed to have more severe symptoms and a different symptom profile, including apparently typical development before regression, faster regression, more affective symptoms, and more global developmental deficit. Possible genetic and autoimmune neurobiological mechanisms were identified. Interpretation: There is limited high‐quality evidence describing the aetiology and outcomes of CDD. However, given the qualitative and prognostic differences between ASD and CDD, we recommend that future diagnostic criteria should distinguish late‐onset regression. What this paper adds: More than 90% of participants with childhood disintegrative disorder (CDD) have intellectual, language, and social impairments. CDD and autism spectrum disorder (ASD) share features of core and extra‐diagnostic symptoms. CDD has more severe impairment than ASD (e.g. lower IQ, more epilepsy). Differences in CDD include faster regression, more mental health symptoms, and more global developmental deficit. Gene expression profiles may differ between CDD and ASD. This article is commented on by Rosman on page 503 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. Video Podcast: https://www.youtube.com/watch?v=fMuK1cgm7iU&feature=youtu.be Resumen: Trastorno desintegrativo infantil y trastorno del espectro autista: una revisión sistemática: Objetivo: En un intento de aclarar el debate que rodea la validez diagnóstica del trastorno desintegrativo infantil (TDI), revisamos sistemáticamente sus características y lo comparamos con el trastorno del espectro autista (TEA). Método: Se realizaron búsquedas en cuatro bases de datos (PubMed, PsycINFO, Embase y Web of Science). Los artículos incluidos tenían participantes con TDI, según lo definido por los síntomas presentes en los criterios del Manual diagnóstico y estadístico de trastornos mentales, Cuarta edición, Revisión de texto y Clasificación internacional de enfermedades, Décima revisión. Los grupos de comparación fueron aquellos con TEA y TEA con regresión. Se excluyeron los estudios de caso. Resultados: Se incluyeron 20 artículos, con 96 participantes con TDI (80 varones y 16 mujeres). La mayoría de los estudios fueron de corte transversal. La prevalencia de TDI fue de 1, 1 a 9, 2 por 100.000, con una edad media de regresión de 3 años a 2 meses (DS 1 años 1 mes), con un rango de 2 años a 7 años. Además de los síntomas centrales de la TDI, la mayoría tenía deterioro intelectual, ansiedad, comportamientos desafiantes y regresión en las habilidades para ir al baño. Los participantes con TDI y TEA compartieron funciones básicas comunes de diagnóstico y de diagnóstico adicional. Sin embargo, los participantes con TDI parecían tener síntomas más graves y un perfil de síntomas diferente, incluido un desarrollo aparentemente típico antes de la regresión, una regresión más rápida, síntomas más afectivos y un déficit de desarrollo más global. Se identificaron posibles mecanismos genéticos y autoinmunes neurobiológicos. Interpretación: Existe una evidencia limitada de alta calidad que describe la etiología y los resultados de la TDI. Sin embargo, dadas las diferencias cualitativas y pronósticas entre la TEA y la TDI, recomendamos que los criterios diagnósticos futuros distingan la regresión de inicio tardío. Abstract : Transtorno desintegrativo da infância e transtorno do espectro autista: uma revisão sistemática: Objetivo: Na tentativa de esclarecer o debate em torno da validade diagnóstica do transtorno desintegrativo da infância (TDI), nós revisamos sistematicamente suas características e as comparamos com o transtorno do espectro autista (TEA). Método: Quatro bases de dados foram pesquisadas (PubMed, PsycINFO, Embase, e Web of Science). Os artigos incluídos tinham participantes com TDI, como definido pelos sintomas presentes nos critérios do Manual Diagnóstico e Estatístico de Transtornos Mentais, quarta edição, com revisão do texto, e na Classificação Internacional de Doenças, 10a edição. Grupos de comparação foram aqueles com TEA e TEA com regressão. Estudos de caso foram excluídos. Resultados: Vinte artigos, incluindo 96 participantes com TDI (80 do sexo masculino, 16 do sexo feminino), foram incluídos. A maior parte dos estudos era transversal. A prevalência de TDI foi de 1, 1 a 9, 2 por 100.000, com idade média de regressão de 3 anos e 2 meses (DP 1a 1m), com variação de 2 anos a 7 anos. Além dos sintomas centrais de TDI, a maioria tinha deficiência intelectual, ansiedade, comportamentos desafiadores, e regressão na habilidade de usar o banheiro. Participantes com TDI e TEA compartilham aspectos diagósticos e extra‐diagnósticos centrais. No entanto, os participantes com TDI pareceram ter sintomas mais severos e um perfil diferente de sintomas, incluindo desenvolvimento aparentemente típico antes da regressão, regressão mais rápida, mais sintomas afetivos, e maior déficit global do desenvolvimento. Possíveis mecanismos neurobiológicos genéticos e autoimunes foram identificados. Interpretação: Há evidência limitada de alta qualidade descrevendo a etiologia dos resultados do TDI. No entanto, dadas as diferenças qualitativas e prognósticas entre TEA e TDI, recomendamos que futuros critérios diagnósticos distinguam a regressão de início tardio.